Computational intelligence in security for information systems 4th international conference, CISIS 2011, Held at IWANN 2011, Torremolinos-Málaga, Spain, June 8-10, 2011. proceedings - International conference on computational intelligence in security for information systems 2011 Torremolinos, Spain); Herrero, Álvaro; Corchado, Emilio; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Computational Intelligence in Security for Information Systems, CISIS 2011, held in Torremolinos-Málaga, in June 2011 as a satellite event of IWANN 2011, the International Work-Conference on Artificial and Natural Neural Networks. The 38 revised full papers presented were carefully reviewed and selected from a total of 70 submissions. The papers are organized in topical sections on machine learning and intelligence, network security, cryptography, securing software, and applications of intelligent methods for security.
Electronic reproduction.
Keywords: Computer security -- Congresses; Computational intelligence -- Congresses; Electronic books